Navigating Global Cyberspace: An Extensive Bibliometric Journey through Digital Financial Literacy and Accounting Research - Azaria, Candra; Noviani, Leny (East Asian Journal of Multidisciplinary Research, 2024)
Despite the growing interest in digital financial literacy and accounting research, there is a lack of a comprehensive summary in the literature. This study aims to fill this gap by providing an up-to-date overview of the literature on digital financial literacy and accounting. Using the PRISMA protocol and VOSViewer, we analyze extensive data from Scopus spanning 2013 to 2024. Similarly, this study encompasses of co-occurrence and co-authorship analyses. The findings show a significant increase in related research, reaching its peak in 2023, driven by increased publishing opportunities and efforts, particularly in Asia and the United States. Strong organizational support, such as universities and funding sponsors, also contributes to this growth. In conclusion, this study offers a clear synthesis of the literature on digital financial literacy and accounting, suggesting potential areas for future research.